The Impact of Using Online Learning Platforms on Student Learning Motivation - Emma Clark; Olivia Davis; Sara Al-Jabri (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid growth of online learning platforms has significantly impacted educational practices globally, particularly in enhancing student learning motivation. Purpose. This study explores the effect of utilizing online learning platforms on students’ motivation to learn, considering their engagement, learning strategies, and academic performance. The primary aim of this research is to analyze how the use of such platforms influences students’ intrinsic and extrinsic motivation within the context of various educational settings. Method. This study adopts a quantitative research approach, using surveys and questionnaires administered to a sample of students from different educational institutions. Data collected were analyzed using descriptive statistics and inferential analysis to determine the relationship between online learning platform usage and students’ motivation levels. Results. The findings reveal a positive correlation between online learning platform usage and increased motivation, particularly in terms of fostering self-regulation, engagement, and a greater sense of autonomy in learning. Students reported higher motivation to participate in lessons and complete assignments when using these platforms. Conclusion. In conclusion, integrating online learning platforms into traditional education methods can significantly enhance students’ learning motivation, supporting both their academic success and personal growth. Future studies should focus on long-term effects and the comparative benefits of different platforms.